A High‐Throughput Search for Functionally Stable Interfaces in Sulfide Solid‐State Lithium Ion Conductors. Issue 21 (24th April 2019) - Fitzhugh, William; Wu, Fan; Ye, Luhan; Deng, Wenye; Qi, Pengfei; Li, Xin
Abstract: Interfacial reactions between ceramic‐sulfide solid‐electrolytes and common electrodes have remained a major impediment to the development of solid‐state lithium‐ion batteries. In practice, this means that ceramic‐sulfide batteries require a suitable coating material to isolate the electrolyte from the electrode materials. In this work, the interfacial stability of Li10 SiP2 S12 with over 67 000 materials is computationally evaluated. Over 2000 materials that are predicted to form stable interfaces in the cathode voltage range and over 1000 materials for the anode range are reported on and cataloged. LiCoO2 is chosen as an example cathode material to identify coating compounds that are stable with both Li10 SiP2 S12 and a common cathode. The correlation between elemental composition and multiple instability metrics (e.g., chemical/electrochemical) is analyzed, revealing key trends in, amongst others, the role of anion selection. A new binary‐search algorithm is introduced for evaluating the pseudo‐phase with improved speed and accuracy. Computational challenges posed by high‐throughput interfacial phase‐diagram calculations are highlighted as well as pragmatic computational methods to make such calculations routinely feasible. In addition to the over 3000 materials cataloged, representative materials from the anionic classes of oxides, fluorides, and sulfides are chosen to experimentally demonstrate chemical stability when in contact with Li10 SiP2 S12 . Abstract : In this work, high‐throughput analysis of density functional theory phase data is used to understand the interface decomposition in solid‐state batteries based on ceramic sulfides. Elemental analysis reveals key trends in the relation between composition and susceptibility for decay. Large‐scale electrochemical analysis provides over 3000 materials that are predicted to form stable interfaces with Li10 SiP2 S12 .